The geography of creative people in Germany revisited - Michael Fritsch; Michael Stuetzer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
It has been argued that creativity is an important source of regional growth. This paper investigates the geography of people in creative occupation in Germany. The population share of the creative class as well as of bohemians and artists is relatively high in larger cities, but smaller places and rural regions may also have a considerable proportion of people with a creative job. While ethnical and cultural diversity and high availability of public health care and education can explain the distribution of creative people, employment opportunities seem to play only a minor role.
Keywords: O31; O18; R11; 330; creativity; entrepreneurship; innovation; regional development